2013
DOI: 10.1111/milq.12005
|View full text |Cite
|
Sign up to set email alerts
|

New Evidence on the Allocation of NIH Funds across Diseases

Abstract: and Disease Categorization) database on funding for 107 diseases in 2008 and linked these to data on deaths and hospitalizations for these diseases. We used RCDC data and information from another NIH database-RePORTER-to determine institute-specific funding for these diseases and also funding by award type. We used these data to examine the overall responsiveness of NIH funding to disease burden, within-institute responsiveness, and the responsiveness of different types of NIH awards.Findings: Overall, we foun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
44
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(45 citation statements)
references
References 14 publications
(20 reference statements)
1
44
0
Order By: Relevance
“…HIV/AIDS, dementia, diabetes mellitus, breast cancer and perinatal conditions all received more funding from NIH than would be expected based on US disease burden, whereas depression, injuries and chronic obstructive pulmonary disorder were relatively underfunded. Sampat et al 5 later undertook an expanded study of 107 diseases and found a statistically significant positive relationship between clinical trial funding and deaths or days in hospital. In another study, Vanderelst et al 6 specifically looked at data from low-income countries and found a weak association (r=0.1) between disease burden and funding.…”
Section: To the Editormentioning
confidence: 99%
“…HIV/AIDS, dementia, diabetes mellitus, breast cancer and perinatal conditions all received more funding from NIH than would be expected based on US disease burden, whereas depression, injuries and chronic obstructive pulmonary disorder were relatively underfunded. Sampat et al 5 later undertook an expanded study of 107 diseases and found a statistically significant positive relationship between clinical trial funding and deaths or days in hospital. In another study, Vanderelst et al 6 specifically looked at data from low-income countries and found a weak association (r=0.1) between disease burden and funding.…”
Section: To the Editormentioning
confidence: 99%
“…However, as the Institute of Medicine (1998), Dresser (1999), and Sampat et al (2013) suggest, some grant mechanisms at the NIH-particularly RFAs and PAs-are more focused and allow the NIH to steer the direction of research in response to congressional guidance. RFAs and PAs are solicitations by the NIH for grant applications that address a defined research topic.…”
Section: Grant Mechanisms At the Nihmentioning
confidence: 97%
“…For example, many grants referenced a rare disease in the title and abstract but not in the thesaurus keywords, and many rare diseases did not have entries in the CRISP thesaurus. 13 Historically, the NIH has not reported data on funding by disease, but the agency's recent Research, Condition, and Disease Categorization (RCDC) initiative tabulates disease-specific funding data for a subset of diseases and for the years after 2007 (Sampat 2012, Sampat et al 2013. For the 33 diseases in our sample also listed on the RCDC, we compared our funding numbers for the year 2008 to those available from the RCDC (see Figure A1 of the supplementary appendix).…”
Section: Agency Funding For Rare Diseasesmentioning
confidence: 97%
See 1 more Smart Citation
“…This could be of concern to policymakers and other key stakeholders. Relevant government and funding agencies should be aware of these ongoing trends and might have to rethink immigration policy, make available more federal funding for major scientific research initiatives, which are both basic and applied in nature 25 , and continue reinforcing the US innovation ecosystems and scientific entrepreneurship in the face of increasing global C A R E E R S A N D R E C R U I T M E N T npg…”
Section: Competing Financial Interestsmentioning
confidence: 99%